Tübingen model study: large-scale introduction of rapid antigen testing in the population and the viral dynamics of SARS-CoV-2 - Ayran, Jule; Köhler, Carsten; Linh, Le Thi Kieu; Schneider, Gisela; Pallerla, Srinivas Reddy; Battke, Florian; Federle, Lisa; Martus, Peter; Kremsner, Peter G.; Velavan, Thirumalaisamy P. (Frontiers in Public Health, 2023)
Despite of contact restrictions, population mobility remains the main reason for the spread of SARS-CoV-2. The state of Baden-Württemberg (BW), Germany, approved a model study in Tübingen (TÜMOD) to evaluate how mandatory rapid diagnostic tests (RDT) could reduce transmission. Between 16 March and 24 April 2021, approximately 165,000 residents and visitors to the city were screened for SARS CoV-2 infection using Abbott Panbio™ COVID-19 Antigen rapid test device. We assessed incidences and recorded epidemiological characteristics in a subset of 4118 participants recruited at three of the nine testing stations. PCR tests were performed in RDT-positives to determine the positive predictive value (PPV), and circulating variants of SARS-CoV-2 were identified by whole-genome sequencing. 2282 RDT-negative samples were tested by pooled PCR to calculate the false negative rate (FNR). Viral load was compared between variants. 116 (3%) participants were positive by RDT, and of these, 57 (49%) were positive by PCR, 55 (47%) were negative. This resulted in a PPV of 51%. Of the 57 positives, 52 SARS-CoV-2 genomes were successfully sequenced. Of these, 50 belonged to the B.1.1.7 lineage, which had a high viral load (average Ct = 19). Of the 2282 RDT negatives tested, all were PCR negative (FNR 0%). At the end of TÜMOD, the incidence in Tübingen, which was initially lower, had reached the incidence in the state of BW. While it is difficult to assess the impact of TÜMOD on incidence independent of confounding factors, modelling suggests a favourable effect of close-meshed testing on infection rates.